Influence of customer pressure on the innovative activity of a company - Tomaszewski, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
This article is based on the research conducted on the companies from five countries: Latvia, Lithuania, Russia, Estonia and Poland. These countries are all located in the south-eastern part of the Baltic Sea. A review of the literature reveals no analysis of the intensity of customer impact on the innovative activity of a company. In this context, the main aim of the article is to analyse the influence and intensity of types of customer pressure on the innovative activity of a company. This article takes into account both the pressure from customers to introduce new products and the pressure from customers to lower the production costs. The research hypothesis allowing the attainment of the research goal is formulated as follows: The majority of innovations introduced by the companies from the countries of south-east part of the Baltic Sea are demand-driven, that is, they are a result of customer pressure. This means that the probability of occurrence of all the analysed attributes of innovative activity depends on the amount of pressure on the side of customers. With no pressure, the probability of occurrence of the analysed attributes of innovative activity is smallest
Argumenta Oeconomica, 2015, Nr 2 (35), s. 203-219
Keywords: customer pressure; innovative activity; demand-driven innovation